Benefits and Enjoyment of a Swimming Intervention for Youth With Cerebral Palsy: An RCT Study. Issue 2 (2016) - Declerck, Marlies; Verheul, Martine; Daly, Daniel; Sanders, Ross
Abstract : Purpose: To investigate enjoyment and specific benefits of a swimming intervention for youth with cerebral palsy (CP). Methods: Fourteen youth with CP (aged 7 to 17 years, Gross Motor Function Classification System levels I to III) were randomly assigned to control and swimming groups. Walking ability, swimming skills, fatigue, and pain were assessed at baseline, after a 10-week swimming intervention (2/week, 40-50 minutes) or control period, after a 5-week follow-up and, for the intervention group, after a 20-week follow-up period. The level of enjoyment of each swim-session was assessed. Results: Levels of enjoyment were high. Walking and swimming skills improved significantly more in the swimming than in the control group ( P = .043; P = .002, respectively), whereas fatigue and pain did not increase. After 20 weeks, gains in walking and swimming skills were retained ( P = .017; P = .016, respectively). Conclusion: We recommend a swimming program for youth with CP to complement a physical therapy program. Abstract : Supplemental Digital Content is Available in the Text.A swimming program for youth with cerebral palsy to complement a physical therapy program is explored.